Human impact on Holocene sediment dynamics in the Eastern Mediterranean – the example of the Roman harbour of Ephesus. Issue 7 (1st April 2016) - Stock, Friederike; Knipping, Maria; Pint, Anna; Ladstätter, Sabine; Delile, Hugo; Heiss, Andreas G.; Laermanns, Hannes; Mitchell, Piers D.; Ployer, René; Steskal, Martin; Thanheiser, Ursula; Urz, Ralf; et al.
Abstract: During the past millennia, many erosion and accumulation processes have been modified by anthropogenic impact. This holds especially true for the environs of ancient settlements and their harbours along the Mediterranean coasts. Our multi‐proxy investigations in the Roman harbour and the harbour canal of Ephesus (western Turkey) reveals that humans have significantly triggered soil erosion during the last three millennia. Since the eighth centurybc, and especially since the Hellenistic period, a high sedimentation rate indicates fast alluviation and delta progradation of the Küçük Menderes. Deforestation, agriculture (especially ploughing) and grazing (especially goats) were the main reasons for erosion of the river catchment area. One consequence was significant siltation of the Hellenistic/Roman harbour basin. This sediment trap archives the human impact, which was strongly enhanced from Hellenistic/Roman to Byzantine times (second/first centuriesbc to the sixth/seventh centuriesad ), evidenced by high sedimentation rates, raised values of heavy metal contaminations [lead (Pb), copper (Cu)], the occurrence of fruit tree pollen and of intestinal parasites. From the middle to the end of the first millenniumad, the influence of Ephesus declined, which resulted in a decrease of human impact. Studies of several ancient settlements around the Mediterranean Sea tell a comparable story. They also confirm that during their most flourishing periods the human impact totally overprinted the climatic one. To detect the latter, geo‐bio‐archives of relatively pristine areas have to be investigated in detail. Copyright © 2016 John Wiley & Sons, Ltd.